Effects of washing procedures in reducing Listeria monocytogenes on raw leafy vegetables - Nguyen, Thi Huong Giang; Mahmud Ab Rashid, Nor-Khaizura; Mahyudin, Nor Ainy; An Vu, Thi Lam (Czech Academy of Agricultural Sciences, 2022)
The efficacy of potable water and antimicrobial agents, including turmeric extract, black pepper extract, sodium chloride and sodium bicarbonate, in reducing Listeria monocytogenes on the leaf mustard (Brassica integrifolia) and iceberg lettuce (Lactuca sativa L.) was compared. The uncontaminated samples of two raw leafy vegetables were inoculated with L. monocytogenes at a concentration of 5 log and 7 log colony-forming units (CFU) g–1 for 1 h. At the high L. monocytogenes contamination level, the treatment with black pepper extract 0.6 mg mL–1 for 5 min was found to produce the most considerable decrease in L. monocytogenes counts, resulting in 1.44 log and 1.68 log reduction on leaf mustard and iceberg lettuce, respectively. Similarly, the black pepper extract also showed the highest L. monocytogenes reduction, approximately 0.79 log CFU g–1 on two leafy vegetables at the low contamination level. However, the odour of black pepper extract was left on the vegetables after being washed.